Trauma experiences of people with an intellectual disability and their implications: A scoping review. Issue 4 (26th March 2021) - McNally, Paddy; Taggart, Laurence; Shevlin, Mark
Abstract: Background: People with an intellectual disability are more vulnerable to psychological trauma compared with the general population. The aim of this scoping review was to identify the current status of the literature on trauma that is specific to the experiences of adults with an intellectual disability, living in community settings. Methods: A scoping review was conducted using the Arksey and O'Malley ( International Journal of Social Research Methodology, 2005, 8, 19) framework. Forty‐one international papers were reviewed spanning 2000–2020, and their quality assessed using the MMAT. Findings: (1) Aggressive behaviours can be symptoms of trauma, (2) there are appropriate assessment tools for the impact of trauma, (3) evidence‐based interventions for trauma may be effective, and (4) factors associated with disability can be experienced as traumatic. Conclusion: There is a growing body of literature highlighting assessment needs and potential interventions for people with an intellectual disability who have experienced psychological trauma. Further research is needed to develop trauma‐informed pathways.